(untitled) (Journal of Engineering, 2010)
The present study deals with the removal of oil from wastewater by organoclay. The organoclay was prepared by combination of Iraqi bentonite with quaternary amine (hexadecyltrimethyl ammonium chloride). The wastewater samples were obtained from the washing unit of fuel oil in the "South Baghdad Gas Power Plant. The operating conditions of batch process for removal of oil from wastewater by using the prepared organoclays were studied in details (quantity of organoclay, mixer speed and time of adsorption). Initial concentration of wastewater used in this study was within a maximum range of 230-1512 mg/L. XRD and FTIR diagram of the prepared organoclay showed a considerable differences from those for natural bentonite which indicates the exchange of quaternary amine with Ca ions at the surface of bentonite. The concentration of oil in the wastewater samples decreased below 10 mg L after treatment with organoclay. Batch kinetics studies were conducted by using kinetic equations (Lagergren and Ho et al) and batch isotherm studies was conducted by using isotherm models (Freundlich. Langmuir and BET)